1988
DOI: 10.1007/bf00332490
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of lead in human hemopoietic tissue and spongy bone after lead poisoning and Ca-EDTA chelation therapy

Abstract: Two iliac crest needle biopsies were taken from a 43-year-old lead-poisoned woman during and after completion of a Ca-EDTA treatment. By atomic absorption spectroscopy the first and second biopsy were found to contain 56, respectively 41.6 micrograms lead/g wet tissue. In both biopsies 36% of the lead was extractable in 0.1 N HCl. Electron microbeam X-ray analysis proved to have too low sensitivity for quantitation of the lead in these biopsies. Laser microbeam mass analysis (LAMMA), performed only on the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The second statement is consistent with the existing literature on the mechanism and kinetics of bone Pb/bone blood exchange [16][17][18][19][20][21][22][23]. The long half-life of Pb in bone is especially relevant to an understanding of the Pb content of the Beechey Island burials, which occurred early in the expedition.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The second statement is consistent with the existing literature on the mechanism and kinetics of bone Pb/bone blood exchange [16][17][18][19][20][21][22][23]. The long half-life of Pb in bone is especially relevant to an understanding of the Pb content of the Beechey Island burials, which occurred early in the expedition.…”
supporting
confidence: 85%
“…Individual metals are displayed using a color scale based on the maximum concentration of the metal; the scale is not normalized in such a way as to allow direct comparison of the concentrations of different metals. While it has been suggested that a detailed study of the Haversion canals in bone may provide a chronology of Pb accumulation [36], the existing literature [16][17][18][19][20][21][22][23] on the kinetics of Pb/bone exchange make it clear that the Pb distribution patterns within bone will provide a realistic chronology of uptake. The significance of the distribution of other metals must be uncertain, though the Beechey Island materials (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the processes giving rise to intermediate-term loss from bone have not been dearly established, either for lead or for the alkaline earth elements. For lead, much of the loss from bone occurring from a few days to a year or more after exposure might result in part from the bone diffusion process generally hypothesized and in part from other processes, such as turnover of lead-binding components of the organic matrix of bone (93) or gradual release of lead from cellular components of bone.…”
Section: Bonementioning
confidence: 99%
“…Also, the data help to explain the rebound in PbB immediately after treatment, which presumably is due to internal redistribution of lead. Even after multiple courses of CaNa2EDTA, body lead stores are likely to remain elevated (13 (14). The Chinese first reported the use of DMSA as an antidote for poisoning due bCalculations: A,= (A/ -e -k' where A, = prechelation lead pool, A, = total lead excreted in 5 days, and k = rate constant.…”
Section: Cana2edta: Human Studiesmentioning
confidence: 99%